Special Issue: Cancer Metastasis and Therapeutic Resistance - Elizabeth S. Yeh (Biomedicines, 2023)
Metastasis and resistance to cancer therapeutics are critical barriers to curing cancer. This special issue entitled “Cancer Metastasis and Therapeutic Resistance” contains nine original contributions. The articles span a variety of human cancers, including breast, lung, brain, prostate, and skin and touch upon significant areas of interest such as cancer stem cell function, cancer immunology, and glycosylation.